Increasing Adherence to Acute Otitis Media Treatment Duration Guidelines using a Quality Improvement Approach. Issue 6 (15th November 2021) - Uhl, Bethany D.; Boutzoukas, Angelique; Gallup, Nathaniel; Patrick, Michael; Stultz, Jerry; Porter, Courtney; Watson, Joshua R.
Abstract : Supplemental Digital Content is available in the text. Abstract : Introduction: This quality improvement initiative aimed to improve American Academy of Pediatrics acute otitis media (AOM) guideline adherence in pediatric urgent care sites by increasing the percentage of patients 2 years and older with AOM who received a short duration (7 days or fewer) of antibiotics from a baseline of 7% to a goal of 50%. Methods: This quality improvement initiative was conducted in a network of seven urgent care sites affiliated with a large academic children's hospital. The interventions focused on clinician and family education, clinical decision support, and a discharge template that defaulted to a 7-day duration of antibiotics for patients 2 years and older diagnosed with AOM. The outcome measure was the percentage of patients receiving 7 days or fewer of antibiotics. The process measure was the percentage of prescriptions originating from the new discharge template. A repeat visit for AOM within 30 days from the initial visit was the balancing measure. Results: The percentage of patients diagnosed with AOM receiving a short antibiotic course increased from a baseline of 7% to a new centerline mean of 67%, which exceeded the goal. This project resulted in 10, 138 antibiotic days being avoided. Eighty-two percent of short-course prescriptions originated from the discharge template. Repeat visits for AOM within 1 month of the initial visit did not increase. Conclusions: A quality improvement initiative combining education and clinical decision support improved adherence to AOM treatment duration guidelines and avoided unnecessary antibiotic exposure in a pediatric urgent care network without increasing treatment failures.